Perception of antibiotic use and antibiotic resistance among faculty and staff in a medical school: insights from a mixed mode survey in Bahrain - Ronni Mol Joji; Archana Prabu Kumar; Amer Almarabheh; Ali Al-Mahmeed; Mohd Shadab; Khalid Bindayna; Mohammad Shahid (BMC Public Health)
Abstract Background Understanding awareness of antibiotics is crucial in identifying the attitudes of people which could subsequently help shape campaigns and policies addressing this problem. The study aimed to explore awareness of antibiotics use and antibiotic resistance among faculty and staff at the medical institution. Methodology All the study participants (faculty & staff) were asked to complete the survey. The survey consisted of questions ranging from knowledge and use of antibiotics to knowledge about antibiotic resistance. Ninety participants responded for the quantitative survey. After the questionnaire administration, in-depth interviews were conducted with subgroups of faculty, technicians, and administrative staff. The researchers employed a purposive sampling strategy. Around 43 participants volunteered to participate in this interview. Results The results showed that 92% of participants reported taking antibiotics, with the majority receiving them from licensed medical providers, while a smaller respondent (12.6%) self-medicated. The concept of “antibiotic resistance” was the most widely recognized, with 47.78% of participants indicating awareness, typically gained from healthcare personnel. The in-depth interviews revealed that the faculty group had the strongest basic knowledge about antibiotics and resistance. When it comes to consequences of ABR, participants mentioned the risk of repeated infection and spread of stronger strains of bacteria that might be difficult to treat soon. The most important suggestion provided by most participants was that the antibiotics should be taken only with a doctor’s prescription and consumed for appropriate duration as suggested by the doctor. Conclusions Although the study revealed a strong understanding of antibiotics, awareness regarding antibiotic resistance remained low. The findings emphasize the importance of enhancing communication skills among health professionals and implementing stewardship programs to promote safe antibiotic use and raise awareness about antibiotic resistance.